High temperature structural adhesive

By using specific components and isocyanate mass ratio adjustment in structural glue, combined with hydrogenated castor oil to modify nano silicon carbide and mullite powder, the problems of poor high temperature resistance and low tensile bonding strength of structural glue are solved, and high temperature is achieved Efficient bonding effect in the environment.

CN118599458BActive Publication Date: 2025-02-14TANGSHAN LIXIA TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410762273.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-13
Publication Date
2025-02-14
Estimated Expiration
2044-06-13

AI Technical Summary

Technical Problem

The existing structural adhesives have poor high temperature resistance and low tensile bonding strength, making it difficult to meet the connection needs in high temperature environments.

Method used

Using components A including epoxy resin, isocyanate and filler and components B of polyester resin and antioxidant, the use of nano-silicon carbide and mullite powder modified by hydrogenation of castor oil is improved by adjusting the mass ratio of different isocyanates. The density and synergistic effect of structural glue.

Benefits of technology

It significantly improves the high temperature resistance and tensile bonding strength of structural adhesives, and can maintain good bonding performance under high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to the technical field of structural adhesives, and proposes a high-temperature structural adhesive, which includes component A and component B. Component A includes the following raw materials in parts by weight: 20-40 parts of epoxy resin, 5-10 parts of isocyanate, and 8-16 parts of filler; component B includes the following raw materials in parts by weight: 10-20 parts of polyester resin, 0.05-1 part of antioxidant; the isocyanate is two or three of isophorone diisocyanate, dimethyl biphenyl diisocyanate, and triphenylmethane triisocyanate. Through the above technical scheme, the problems of poor high temperature resistance and low tensile bonding strength of the structural adhesive in the prior art are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of structural adhesives, and in particular to high-temperature structural adhesives. Background Art

[0002] The connection between many materials mainly relies on structural adhesives, that is, structural glue. Structural adhesives can bond metals, foam boards, fiber products, wood, leather, plastics and other substrates. The adhesive layer after bonding has the characteristics of high hardness, excellent low temperature resistance, good flexibility, etc., which is very suitable for the manufacture of various layered composite board products.

[0003] However, existing structural adhesives generally have the problems of poor high temperature resistance and low tensile bonding strength. Therefore, in order to overcome the above defects in the prior art, a structural adhesive with high temperature resistance and high tensile bonding strength is provided. Summary of the invention

[0004] The present invention provides a high-temperature structural adhesive, which solves the problems of poor high-temperature resistance and low tensile bonding strength of the structural adhesive in the related art.

[0005] The technical solution of the present invention is as follows:

[0006] The present invention provides a high-temperature structural adhesive, comprising a component A and a component B, wherein the component A comprises the following raw materials in parts by weight: 20 to 40 parts of epoxy resin, 5 to 10 parts of isocyanate, and 8 to 16 parts of filler;

[0007] The B component includes the following raw materials in parts by weight: 10-20 parts of polyester resin and 0.05-1 part of antioxidant;

[0008] The isocyanate is two or three of isophorone diisocyanate, dimethyl diphenyl diisocyanate and triphenylmethane triisocyanate.

[0009] As a further technical solution, when the isocyanate is dimethyl diphenyl diisocyanate and triphenylmethane triisocyanate, the mass ratio of the dimethyl diphenyl diisocyanate to triphenylmethane triisocyanate is 8:2-7.

[0010] In the present invention, when the mass ratio of dimethylbiphenyl diisocyanate to triphenylmethane triisocyanate is 8:2-7, the high temperature resistance and tensile bonding strength of the structural adhesive are further improved.

[0011] As a further technical solution, when the isocyanate is isophorone diisocyanate, dimethylbiphenyl diisocyanate and triphenylmethane triisocyanate, the mass ratio of isophorone diisocyanate, dimethylbiphenyl diisocyanate and triphenylmethane triisocyanate is 1~5:4:3.

[0012] In the present invention, when the mass ratio of isophorone diisocyanate, dimethylbiphenyl diisocyanate and triphenylmethane triisocyanate is adjusted to 1-5:4:3, the high temperature resistance and tensile bonding strength of the structural adhesive are further improved.

[0013] As a further technical solution, the epoxy resin includes one or two of alicyclic epoxy resin and aromatic epoxy resin; the antioxidant is one or more of antioxidant 626, antioxidant 1010, antioxidant 168, and antioxidant 1024.

[0014] As a further technical solution, the filler is a hydrogenated castor oil modified filler.

[0015] As a further technical solution, in the hydrogenated castor oil modified filler, the filler consists of nano silicon carbide and mullite powder.

[0016] In the present invention, hydrogenated castor oil modifies nano silicon carbide and mullite powder, thereby improving the combination of nano silicon carbide and mullite powder inside the structural adhesive, and further improving the high temperature resistance and tensile bonding strength of the structural adhesive.

[0017] As a further technical solution, the mass ratio of the nano silicon carbide to mullite powder is 3:1-7.

[0018] In the present invention, when the mass ratio of nano silicon carbide to mullite powder is adjusted to 3:1-7, the high temperature resistance of the structural adhesive is further improved.

[0019] As a further technical solution, the preparation method of the filler comprises the following steps: dissolving hydrogenated castor oil and mixing it with the filler, removing the solvent, and obtaining the filler;

[0020] The mass ratio of the filler to hydrogenated castor oil is 15-24:1.

[0021] The present invention also provides a method for preparing the high temperature structural adhesive, comprising the following steps:

[0022] S1, mixing the raw materials of component A to obtain component A;

[0023] S2, mixing the raw materials of component B to obtain component B;

[0024] S3. Mix the component A and the component B in a mass ratio of 1-3:1 to obtain a structural adhesive.

[0025] As a further technical solution, in step S3, the mixing temperature is 80-100°C and the mixing time is 2-3h.

[0026] The working principle and beneficial effects of the present invention are:

[0027] In the present invention, two or three of isophorone diisocyanate, dimethyl diphenyl diisocyanate and triphenylmethane triisocyanate are introduced into component A of the high-temperature structural adhesive, and after being mixed with component B, the internal density of the structural adhesive is improved, and the different polyisocyanates work synergistically, thereby significantly improving the high temperature resistance and tensile bonding strength of the structural adhesive. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] In the following examples and comparative examples, the model of epoxy resin is RD137; the model of polyester resin is 196; the particle size of nano-silicon carbide is 50 nm; the particle size of mullite powder is 3000 mesh; hydrogenated castor oil was purchased from Jinan Xiangfeng Weiye Chemical Co., Ltd.

[0030] Example 1

[0031] High temperature structural adhesive, component A includes the following raw materials in parts by weight: 20 parts of epoxy resin, 5 parts of isocyanate, 1.6 parts of nano silicon carbide, and 6.4 parts of mullite powder;

[0032] Component B includes the following raw materials in parts by weight: 10 parts of polyester resin, 0.05 parts of antioxidant 626;

[0033] Wherein, the isocyanate is isophorone diisocyanate and dimethyl diphenyl diisocyanate in a mass ratio of 1:9;

[0034] The preparation method of high temperature structural adhesive comprises the following steps:

[0035] S1, mixing the raw materials of component A to obtain component A;

[0036] S2, mixing the raw materials of component B to obtain component B;

[0037] S3. Mix component A and component B at a mass ratio of 3:1 at 80° C. for 3 h to obtain a structural adhesive.

[0038] Example 2

[0039] High temperature structural adhesive, component A includes the following raw materials in parts by weight: 40 parts of epoxy resin, 10 parts of isocyanate, 3.2 parts of nano silicon carbide, and 12.8 parts of mullite powder;

[0040] Component B includes the following raw materials in parts by weight: 20 parts of polyester resin, 1 part of antioxidant 626;

[0041] Wherein, the isocyanate is isophorone diisocyanate and dimethyl diphenyl diisocyanate in a mass ratio of 9:1;

[0042] The preparation method of high temperature structural adhesive comprises the following steps:

[0043] S1, mixing the raw materials of component A to obtain component A;

[0044] S2, mixing the raw materials of component B to obtain component B;

[0045] S3. Mix component A and component B at a mass ratio of 2:1 at 100° C. for 2 h to obtain a structural adhesive.

[0046] Example 3

[0047] High temperature structural adhesive, component A includes the following raw materials in parts by weight: 30 parts of epoxy resin, 7.5 parts of isocyanate, 2 parts of nano silicon carbide, and 8 parts of mullite powder;

[0048] Component B includes the following raw materials in parts by weight: 15 parts of polyester resin, 1 part of antioxidant 626;

[0049] Wherein, the isocyanate is isophorone diisocyanate and triphenylmethane triisocyanate in a mass ratio of 9:1;

[0050] The preparation method of high temperature structural adhesive comprises the following steps:

[0051] S1, mixing the raw materials of component A to obtain component A;

[0052] S2, mixing the raw materials of component B to obtain component B;

[0053] S3. Mix component A and component B at a mass ratio of 1:1 at 90° C. for 3 hours to obtain a structural adhesive.

[0054] Example 4

[0055] The only difference between this embodiment and embodiment 3 is that the isocyanate is dimethyl diphenyl diisocyanate and triphenylmethane triisocyanate in a mass ratio of 9:1.

[0056] Example 5

[0057] The only difference between this embodiment and embodiment 3 is that the isocyanate is dimethyl diphenyl diisocyanate and triphenylmethane triisocyanate in a mass ratio of 7:8.

[0058] Example 6

[0059] The only difference between this embodiment and embodiment 3 is that the isocyanate is dimethyl diphenyl diisocyanate and triphenylmethane triisocyanate in a mass ratio of 8:2.

[0060] Example 7

[0061] The only difference between this embodiment and embodiment 3 is that the isocyanate is dimethyl diphenyl diisocyanate and triphenylmethane triisocyanate in a mass ratio of 8:7.

[0062] Example 8

[0063] The only difference between this embodiment and embodiment 3 is that the isocyanate is isophorone diisocyanate, dimethyl diphenyl diisocyanate and triphenylmethane triisocyanate in a mass ratio of 1:5:3.

[0064] Example 9

[0065] The only difference between this embodiment and embodiment 3 is that the isocyanate is isophorone diisocyanate, dimethyl diphenyl diisocyanate and triphenylmethane triisocyanate in a mass ratio of 6:4:3.

[0066] Example 10

[0067] The only difference between this embodiment and embodiment 3 is that the isocyanate is isophorone diisocyanate, dimethyl diphenyl diisocyanate and triphenylmethane triisocyanate in a mass ratio of 1:4:3.

[0068] Embodiment 11

[0069] The only difference between this embodiment and embodiment 3 is that the isocyanate is isophorone diisocyanate, dimethyl diphenyl diisocyanate and triphenylmethane triisocyanate in a mass ratio of 5:4:3.

[0070] Example 12

[0071] The difference between this embodiment and embodiment 11 is that the nano silicon carbide and mullite powder in component A of the high temperature structural adhesive are nano silicon carbide and mullite powder modified by hydrogenated castor oil;

[0072] The modification method comprises the following steps: dissolving hydrogenated castor oil in chloroform, adding filler and mixing, and removing chloroform to obtain the modified castor oil; wherein the total mass of nano silicon carbide and mullite powder is 20 times the mass of hydrogenated castor oil, and the mass-to-volume ratio of hydrogenated castor oil and chloroform is 1g:15mL.

[0073] Example 13

[0074] The only difference between this embodiment and embodiment 12 is that in component A of the high temperature structural adhesive, nano silicon carbide accounts for 8 parts and mullite powder accounts for 2 parts.

[0075] Embodiment 14

[0076] The only difference between this embodiment and embodiment 12 is that in component A of the high temperature structural adhesive, nano silicon carbide accounts for 7.5 parts and mullite powder accounts for 2.5 parts.

[0077] Embodiment 15

[0078] The only difference between this embodiment and embodiment 12 is that in component A of the high temperature structural adhesive, nano silicon carbide accounts for 3 parts and mullite powder accounts for 7 parts.

[0079] Comparative Example 1

[0080] The only difference between this comparative example and Example 3 is that the isocyanate is isophorone diisocyanate.

[0081] Comparative Example 2

[0082] The only difference between this comparative example and Example 3 is that the isocyanate is dimethyl diphenyl diisocyanate.

[0083] Comparative Example 3

[0084] The difference between this comparative example and Example 3 is that the isocyanate is triphenylmethane triisocyanate.

[0085] The structural adhesive prepared in Example 3 was cured at room temperature, and various performance tests were performed after curing at room temperature for 24 hours. The test results are shown in Table 1.

[0086] Table 1 Performance test results

[0087]

[0088] The structural adhesives prepared in Examples 1 to 2, Examples 4 to 15 and Comparative Examples 1 to 3 were tested for their tensile bond strength at 23°C without high temperature treatment and their tensile bond strength after high temperature treatment at 100°C for 24 hours according to the testing method of Example 3, and the change rate of tensile bond strength was calculated. The change rate of tensile bond strength = [(tensile bond strength without high temperature treatment - tensile bond strength after high temperature treatment) / tensile bond strength without high temperature treatment] × 100%. The test results are shown in Table 2.

[0089] Table 2 Tensile bond strength test results

[0090]

[0091] By comparing the data of Examples 1 to 15 and Comparative Examples 1 to 3, it is found that compared with Comparative Examples 1 to 3, the high-temperature structural adhesives prepared in Examples 1 to 15 have higher tensile bonding strength and a smaller change rate of tensile bonding strength, indicating that the structural adhesives are based on epoxy resin and polyester resin, and the introduction of two or three of isophorone diisocyanate, dimethyl diphenyl diisocyanate, and triphenylmethane triisocyanate can significantly improve the high temperature resistance and tensile bonding strength of the structural adhesives.

[0092] By comparing the data of Examples 3 to 7, it is found that compared with Examples 3 to 5, the tensile bonding strength of the structural adhesives prepared in Examples 6 to 7 is higher and the change rate of the tensile bonding strength is smaller, indicating that when the mass ratio of dimethyl diphenyl diisocyanate to triphenylmethane triisocyanate is 8:2 to 7, the high temperature resistance and tensile bonding strength of the structural adhesive can be further improved.

[0093] By comparing the data of Examples 9 to 11, it is found that compared with Examples 9 to 10, the tensile bonding strength of the structural adhesives prepared in Examples 10 to 11 is higher and the change rate of the tensile bonding strength is smaller, indicating that when the mass ratio of isophorone diisocyanate, dimethyl diphenyl diisocyanate and triphenylmethane triisocyanate is adjusted to 1 to 5:4:3, the high temperature resistance and tensile bonding strength of the structural adhesive are further improved.

[0094] By comparing the data of Examples 11 to 15, it is found that compared with Example 11, the tensile bonding strength of the structural adhesives prepared in Examples 12 to 15 is higher and the change rate of the tensile bonding strength is smaller, indicating that hydrogenated castor oil-modified nano-silicon carbide and mullite powder can further improve the high temperature resistance and tensile bonding strength of the structural adhesive; the tensile bonding strength change rate of the structural adhesive prepared in Examples 14 to 15 is smaller, indicating that when the mass ratio of nano-silicon carbide and mullite powder is adjusted to 3:1 to 7, the high temperature resistance of the structural adhesive can be further improved.

[0095] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. High temperature structural adhesive, characterized in that: The method comprises component A and component B, wherein component A comprises the following raw materials in parts by weight: 20 to 40 parts of epoxy resin, 5 to 10 parts of isocyanate, and 8 to 16 parts of filler; The B component includes the following raw materials in parts by weight: 10-20 parts of polyester resin and 0.05-1 part of antioxidant; The isocyanate is two or three of isophorone diisocyanate, dimethyl diphenyl diisocyanate, and triphenylmethane triisocyanate; The mass ratio of the A component to the B component is 1-3:

1.

2. The high temperature structural adhesive according to claim 1, characterized in that: When the isocyanate is dimethyl diphenyl diisocyanate and triphenylmethane triisocyanate, the mass ratio of the dimethyl diphenyl diisocyanate to triphenylmethane triisocyanate is 8:2-7.

3. The high temperature structural adhesive according to claim 1, characterized in that: When the isocyanate is isophorone diisocyanate, dimethylbiphenyl diisocyanate and triphenylmethane triisocyanate, the mass ratio of isophorone diisocyanate, dimethylbiphenyl diisocyanate and triphenylmethane triisocyanate is 1-5:4:

3.

4. The high temperature structural adhesive according to claim 1, characterized in that: The epoxy resin includes one or both of alicyclic epoxy resin and aromatic epoxy resin; the antioxidant is one or more of antioxidant 626, antioxidant 1010, antioxidant 168, and antioxidant 1024.

5. The high temperature structural adhesive according to claim 1, characterized in that: The filler is a hydrogenated castor oil modified filler.

6. The high temperature structural adhesive according to claim 5, characterized in that: In the hydrogenated castor oil modified filler, the filler consists of nano silicon carbide and mullite powder.

7. The high temperature structural adhesive according to claim 6, characterized in that: The mass ratio of the nano silicon carbide to the mullite powder is 3:1-7.

8. The high temperature structural adhesive according to claim 6, characterized in that: The preparation method of the hydrogenated castor oil modified filler comprises the following steps: dissolving hydrogenated castor oil, mixing with nano silicon carbide and mullite powder, and removing the solvent to obtain the hydrogenated castor oil modified filler; The mass ratio of the total mass of the nano-silicon carbide and mullite powder to the hydrogenated castor oil is 15-24:

1.

9. The method for preparing a high temperature structural adhesive according to any one of claims 1 to 8, characterized in that: The steps include: S1, mixing the raw materials of component A to obtain component A; S2, mixing the raw materials of component B to obtain component B; S3. Mix the component A and the component B in a mass ratio of 1-3:1 to obtain a structural adhesive.

10. The method for preparing a high temperature structural adhesive according to claim 9, characterized in that: In step S3, the mixing temperature is 80-100° C. and the mixing time is 2-3 hours.

Citation Information

Patent Citations

  • Hot-melt adhesive sheet

    JP2024043757A

  • KR1019029550000B1